Mutation analysis of mthfr gene in Indian women with unexplained recurrent miscarriages; Folic acid supplementation improves pregnancy outcomes - Gupta N.J.; Gupta G.; Chakrabarti S.K.; Thangaraj K.; Singh L.; Chakravarty B. (My University, 2025)
Recurrent pregnancy loss (RPL) is classically defined as the occurrence of two or more consecutive clinically recognized pregnancy losses that end prior to twenty weeks. The cause(s) of RPL are elusive, often idiopathic, and multifactorial that is frustrating for the couples and the physicians. Many RPL results from chromosomal or genetic abnormalities and are random events. Methylenetetrahydrofolate reductase (MTHFR) C677T gene polymorphisms have been shown to be associated with many cases of RPL. The activity of the MTHFR enzyme is markedly reduced in people with C677T gene polymorphisms that decreases the conversion of homocysteine into methionine resulting in homocysteine accumulation in the blood, a condition known as hyperhomocysteinemia that has been described as a risk factor for the idiopathic RPL or recurrent miscarriages, however its role has not been firmly established in RPL till date. Furthermore, plasma folic acid levels have been observed to be lower in individuals with (MTHFR) C677T genotype. In the present study, we investigated the role of MTHFR C677T polymorphism in hyperhomocysteinemia leading to RPL in Indian women. Moreover, the effect of folic acid supplementation on RPL in Indian women with MTHFR C677T polymorphism was also investigated. Indian female patients of various age groups (24-39 years) with unexplained recurrent miscarriages including PCOS were selected (case group) for this study. They were genotyped for MTHFR C677T polymorphisms and homocysteine levels in the plasma were also measured. A total of 302 Indian female patients with the history of recurrent miscarriage/RPL were studied along with 100 control patients. Female patients with no PCOS were selected as control group for this study. Written consents were taken from all the patients. Peripheral blood from the patients was collected and the plasma homocysteine levels were measured. MTHFR C677T polymorphism was measured using sequencer and Restriction Fragment Length Polymorphism (RFLP). 21% of cases were found to be heterozygous for the point mutation at 677 C > T in MTHFR gene. All of them had elevated homocysteine levels. Odds Ratio (OR) was found to be 2.2405 at 95% of confidence interval (CI) and the Risk ratio was observed to be 1.9476, thereby indicating a strong positive correlation between the mutation and the RPL as observed in this study. Thus, the detection of wild type, homozygous/heterozygous status of mutation 677 C > T in the patients could predict risk factors for miscarriages and subsequent fetal health foundation. Furthermore, the mutational analysis will also be helpful to identify possible correlation with other health complications and diseases through case studies. Moreover, in this study we observed beneficial effect of folic acid supplementation in lowering homocyteine levels in patients with RPL. However, large prospective randomized clinical trials are needed to further ascertain the beneficial role of folic acid supplementation in the precise management of RPL. © 2021 Nova Science Publishers, Inc. All rights reserved.